The Effectiveness of metaphoric associative card workshop - Syarifah Nur Alya Syed Mohd Asri; Sheau, Tsuey Chong; Siew, Wen Loh (Penerbit Universiti Kebangsaan Malaysia, 2024)
Metaphoric associative card is a well-known communication tool that is used in various fields such as therapy, consultation and pedagogy. Nowadays, its usage is expanding in Malaysia. This type of picture card is a subjective tool as there is no specific interpretation provided. Hence, training is important in assisting the users. Workshops were organised to provide training to the users regarding the usage of metaphoric associative cards. This research aims to explore the perspectives of workshop participants on the content, materials, advertisement, structure, facilitators and facility of the metaphoric associative workshop conducted by the master trainer of Metaphoric Card Malaysia in Malaysia. The research also examines the impact of the workshop on participants. The informants of this research are five participants who attended the workshop. The researcher employed an in-depth interview method to collect data and a thematic analysis method to analyse the data. The analysis identified the strengths, weaknesses, suggestions and impacts of the workshop. The results indicate that the informants were able to apply what they learned in the workshop. Consequently, this research provides insights for the organiser to conduct better workshops in the future. To conclude, it is recommended that workshop effectiveness evaluation should be conducted frequently to ensure that the workshop content is relevant to the participants and able to attract more people to join.